2010
DOI: 10.1142/s0192415x10008512
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Matrine on Primary and Metastatic Breast Cancer

Abstract: Matrine, one of the main components extracted from a traditional Chinese herb, Sophora flavescens Ait, has displayed anti-cancer activity in several types of cancer cells. This study aims to evaluate the therapeutic benefits of matrine on primary and metastatic breast cancer. Matrine inhibited the viability of and induced apoptosis in human MCF-7 and mouse 4T1 breast cancer cells in a dose-dependent manner in vitro as shown by MTT assay, flow cytometry and laser scanning confocal microscopy. Administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…2), which is consistent with reported findings (57)(58)(59). previous studies demonstrated that Beclin 1 gene transfer decreased the rates of cell proliferation in human breast carcinoma cells and colon cancer cells (34,60), and Beclin 1 heterozygous disruption results in increased cellular proliferation (35).…”
Section: Discussionsupporting
confidence: 93%
“…2), which is consistent with reported findings (57)(58)(59). previous studies demonstrated that Beclin 1 gene transfer decreased the rates of cell proliferation in human breast carcinoma cells and colon cancer cells (34,60), and Beclin 1 heterozygous disruption results in increased cellular proliferation (35).…”
Section: Discussionsupporting
confidence: 93%
“…The antitumor effect of matrine, an alkaloid extracted from Traditional Chinese herbal plants, has been studied in several cancer cell lines (3,(15)(16)(17)(18)20,21,(23)(24)(25). Matrine was found to inhibit the growth of cell lines derived from hepatoma, acute myeloid leukemia, melanoma, gastric carcinoma and lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Matrine has been previously shown to have an inhibitory effect on the growth of several cancer cell lines in vitro (3,(15)(16)(17)(18)20,21,(23)(24)(25). However, it has not been thoroughly explored whether the antitumor property of matrine is also effective on different lung cancer-derived cells.…”
Section: Growth Inhibitory Effect Of Matrine On Lung Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…1), one of the active alkaloids derived from the traditional Chinese herb Sophora alopecuroides L., has potential pharmacological effects including anticarcinogenic and chemopreventive activities on various malignancy cell lines, such as gastric, hepatic, lung, and breast cancers [21,22,23,24]. It also significantly inhibits the proliferation and induces apoptosis of human osteosarcoma and pancreatic cancer cells in vitro and in vivo [25,26].…”
Section: Introductionmentioning
confidence: 99%